Comparative analysis of the anti-radicalism value project model and the conventional model in improving citizen commitment - Tanshzil, Sri Wahyuni; Suryadi, Karim; Komalasari, Kokom; Anggraeni, Leni (Universitas Negeri Yogyakarta, 2023)
This research aims to compare the results of two learning approaches, namely the anti-radicalism value project model and the conventional model, in enhancing the commitment of young citizens. Through data analysis from two groups of classes, the experimental and control groups, we evaluated the outcomes of both learning models on the improvement of young citizens' commitment, including their knowledge, attitudes, and behaviors towards the values and principles of Indonesia's constitutional democracy. By using a combination of qualitative and quantitative research methods, it is hoped that research findings can be reliable. The study shows that the anti-radicalism value project model has significant advantages in increasing the commitment of young citizens compared to the conventional model. Students participating in the project model demonstrated active engagement in the learning process, meaningful learning experiences, and better development of critical thinking skills. On the other hand, the conventional model tends to be limited in providing opportunities for interaction and the active participation of students in the learning process. Students involved in the conventional model are more inclined to be passive recipients of information and less engaged in the learning process. Furthermore, the conventional model also falls short in encouraging students to think critically and relate the subject matter to a real-life context.